PERSEPSI MAHASISWA PROGRAM STUDI PPKn FKIP UNIVERSITAS SRIWIJAYA TERHADAP KONTEN BERITA HOAX DI MEDIA SOSIAL TIKTOK - Deru Kurniawan, Muhammad; Faisal, Emil El (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students’ perceptions of hoax news content on TikTok. This research used a quantitative descriptive approach with a survey method. The respondents were 58 students of the PPKn Study Program, FKIP Universitas Sriwijaya. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics. The results show that students generally have a critical and cautious perception of hoax news content on TikTok, although exposure to hoax information is still frequently encountered. Therefore, strengthening digital literacy among students is essential to prevent the spread of hoax news.